Improved Leader Follower Formation controller for multiple Quadrotors based AFSA - Rabah Abbas; Qinghe Wu (Universitas Ahmad Dahlan, 2015)
In this paper, formation tracking in plane with equal height for all quadrotors is discussed. Two controllers are necessary. First, PID controller is used to ensure the tracking of the desired trajectory by the first quadrotor named leader. The formation of the quadrotors in plane is achieved by using the directed lyapunov controller. In order to improve the controller performances, the artificial fish swarm algorithm is used to ensure the dynamic optimization of the parameter controllers. When the desired shape formation is achieved, PID controller is used again to ensure the keeping of this formation shape. Finally, simulation results demonstrate the effectiveness of the proposed controllers compared to the ordinary controller and also compared to the static optimization by using the same algorithm.